PAST AND PRESENT OF THE PEACE AGENDA WITHIN THE UNITED NATIONS: THE INFLUENCE OF THE SOCIALIST NOTION OF PEACEFUL CO-EXISTENCE - Ch.G. Fernandez; D.F. Puyana (BRICS Law Journal, 2017)
War and peace perpetually alternate and peace is always seen as an endless project, even a dream, to be realised in brotherhood by everyone all over the earth. Present generations should ensure that both they and future generations learn to live together in peace with the highest aspiration of sparing future generations the scourge of war. The UN Charter is the most solemn pact of peace in history, which lays down the necessary basic principles for an enduring peace. Recently, in the context of the joint effort in the recognition of the high importance of practicing tolerance, dialogue, cooperation and solidarity among all human beings, peoples and nations, the General Assembly has raised the voice of victims to strongly condemn war and to openly reiterate their inalienable right to enjoy peace such that all human rights are promoted and protected and development is fully realized.